PROPERTIES OF EUCALYPTUS CAMALDULENSIS DEHNH AND MELIA AZEDARACH L. BRANCHES AND THEIR POTENTIAL FOR UTILIZATION IN WOODY BIOMASS - HUSSEIN , HIZR NOORI; TAHA, MOHAMMEDAMIN Y. (Journal of Duhok University, 2023)
Wood is a magnificent natural resource that can be regarded as the single most important natural resource of the future. Eucalyptus camaldulensis and Melia azedarach trees were introduced in Iraq and planted as ornamental trees at parks and streets. A study of branch wood was conducted in order to identify its basic properties along different level in tree and to highlight its potential utilizations in Duhok- Kurdistan Region of Iraq. Specimens of six trees at three levels (DBH), Diameter at half height (D0.5h) and top level (TL) were collected. In both species, physical properties were significantly affected by tree levels variation (p<0.05), and it was found a higher value in the DBHL (diameter breast height level) compared with other levels for the basic density and moisture content. The value of basic density and moisture content ranged from (0.681 g/cm3) (89.46%) in Eucalyptus camaldulensis to (0.536 g/cm3) (58.01%) in Melia azedarach. There were no significant differences in lignin content or heating value among tree. The physical properties of each species are affected by the level of the branches, while the chemical properties have a slight difference along the tree’s crown. Based on their physical properties, the branches of two types of trees can be used in different manufacturing processes. Depending on the chemical properties and heating value, this branch can be used to obtain the best resources for efficient use of woody biomass